Factors for successful implementation of population-based expanded carrier screening: learning from existing initiatives. (1st August 2016) - Holtkamp, Kim C.A.; Mathijssen, Inge B.; Lakeman, Phillis; van Maarle, Merel C.; Dondorp, Wybo J.; Henneman, Lidewij; Cornel, Martina C.
Abstract: Background: Carrier screening for autosomal recessive disorders aims to facilitate reproductive decision-making by identifying couples with a 1-in-4 risk in every pregnancy of having an affected child. Except for a few countries or regions, carrier screening is not widely offered and is mostly ancestry-based. Technological advances enable carrier screening for multiple diseases simultaneously allowing universal screening regardless of ancestry (population-based expanded carrier screening). It is important to study how this can be successfully implemented. This study therefore aims to identify critical factors involved in successful implementation, from a user perspective, by learning from already implemented initiatives. Methods: Factors associated with successful implementation were identified by: (i) a literature review and (ii) two case studies; studying experiences with carrier screening in two high-risk communities (a Dutch founder population and the Ashkenazi Jewish population), including a survey among community members. Results: Factors identified were familiarity with (specific) genetic diseases and its availability, high perceived benefits of screening (e.g. screening avoids much suffering), acceptance of reproductive options, perceived risk of being a carrier and low perceived social barriers (e.g. stigmatization). In contrast to the Jewish community, the initial demand for screening in the Dutch founder population did not entirely come from the community itself. However, the large social cohesion of the community facilitated the implementation process. Conclusion: To ensure successful implementation of population-based expanded carrier screening, efforts should be made to increase knowledge about genetic diseases, create awareness and address personal benefits of screening in a non-directive way.